Tokenizing Behavior Change: A Pathway for the Sustainable Development Goals - Barclay, Iain; Cooper, Michael; Hackel, Jakob; Perrin, Paul (Frontiers in Blockchain, 2022)
To be successful and sustainable, social impact programs require individuals and groups to change aspects of their behavior. As blockchain-based tokens are increasingly adopted to target social outcomes, it is important to properly define these activities as “behavior change interventions” and assess their design and management as such—otherwise, there is significant risk of possible unintended consequences. Designing tokens as behavior change interventions requires new constructs beyond those currently in use to model the interdependence of digital and social ecosystems, and integration of token engineering, cryptoeconomics, and behavioral skill sets to test token designs within various ecosystems. New token design and testing protocols that integrate behavior measures around the targeted social outcomes are needed, to fill a critical gap in current practice. Hence, new standards, operational frameworks, and ethics are needed to guide the use of tokens at scale, as tools to achieve social impacts such as attaining the United Nations’ Sustainable Development Goals. Meeting these needs requires a collaborative approach between token design actors (computer scientists, cryptoeconomists, token engineers, etc.) and social impact practitioners who will be increasingly called upon to use tokens as behavior change tools. This paper begins to identify common ground and address areas to further develop research and practice of tokens being used for social impact.